Fasies Pengendapan dan Mikroskopis Batubara Seam-A Daerah Senyiur-Muara Wahau, Kab. Kutai Timur, Kalimantan Timur - Basuki Rahmad (Retii, 2022)
The interesting thing from this study is the presence of multiple seams of coal seams in one genetic unit of sediment deposition in the Senyiur Muara Ancalong area, East Kutai, East Kalimantan. Therefore, it is important to study the depositional facies and microscopic properties of coal to be studied. The silicified wood data found in the field inside Seam-1 is in the form of a round lump of silisified wood measuring 30 cm in diameter and a rectangular block of silicified wood measuring 20cmx60 cm. Traces of wood fiber tissue are still visible on the surface of the silisified wood, as well as from the microscopic appearance of wood tissue and quartz resulting from the silicification process. Coal outcrops are found along the Senyiur-Muara Ancalong road, well exposed in the form of a folded wing structure, including the Balikpapan Formation of the Kutai Basin. The results of the measured stratigraphic measurements of coal-bearing sediments consist of repeating claystone inserts of sandstone and coal with a thickness between 0.25 m to 2 m. The results of the proximate analysis of the calorific value of 5711-6233 cal/gr with a vitrinite reflectance value of 0.5 including sub-bituminous rank. The results of microscopic analysis of 2 coal samples containing maceral vitrinite 85.88% vol. (ALC-1) and 88% vol (ALC-2) ; liptinite 4.6% vol. (ALC-1) and 6.4% vol. (ALC-2); inertinite 1% vol. (ALC-1) and 3.8% vol. (ALC-2), the mineral content of pyrite consists of 3.4% vol. (ALC-1) and 5.6% vol. (ALC-2). The coal sediment facies of the study area are located in a delta progradation system which will produce flooded areas in the meandering river system, producing overbank deposits in the form of claystone, crevase splay in the form of layered sandstone, natural levee in the form of alternating silt, sandstone and claystone and sandstone channels at delta plain. The interesting thing from the microscopic nature of the coal is the increase in the maceral content of vitrinite, liptinite and inertinite in the ALC-2 sample and the increase in pyrite mineral in the ALC-2 sample by 5.6% vol. showing framboidal pyrite as pyrite marcasite.